2020
DOI: 10.1177/1971400920975259
|View full text |Cite
|
Sign up to set email alerts
|

Value of high-density sign on CT images after mechanical thrombectomy for large vessel occlusion in predicting hemorrhage and unfavorable outcome

Abstract: Purpose Cerebral hyperdensities can appear on head computed tomography (CT) images performed early after endovascular treatment (EVT) in patients with acute ischemic stroke and may be secondary to contrast staining or hemorrhagic transformation. The aim of this study was to determine how the high-density sign on CT affects mortality and clinical outcome and whether CT parameters predict hemorrhagic conversion or unfavorable outcome. Methods We retrospectively reviewed a database of patients who underwent EVT w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…Some studies found that the presence of a high-density lesion on NCCT had no prognostic value to clinical outcome 8 10 . In contrast, Portela et al 3 found that the total size of the hyperdense area had a positive correlation with 90-day mRS after EVT. As previously reported, the hyperdensity may be related to the contrast agent, hemorrhagic transformation or a combination 9 , 11 , 13 , 17 , which may be caused by varying degrees of BBB disruption.…”
Section: Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“…Some studies found that the presence of a high-density lesion on NCCT had no prognostic value to clinical outcome 8 10 . In contrast, Portela et al 3 found that the total size of the hyperdense area had a positive correlation with 90-day mRS after EVT. As previously reported, the hyperdensity may be related to the contrast agent, hemorrhagic transformation or a combination 9 , 11 , 13 , 17 , which may be caused by varying degrees of BBB disruption.…”
Section: Discussionmentioning
confidence: 81%
“…CE has been commonly found on the NCCT obtained immediately after EVT in patients with AIS 3 10 , which has been attributed to the disruption of the blood brain barrier 4 , 11 13 . In the present study, the incidence of CE on NCCT was 71.5%, which was comparable to prior reports (30.7–87.5% 3 10 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations